THE LIFE OF QUEER INDIVIDUALS IN BAKU, AZERBAIJAN - Aghayev, Aydin (International Journal of Innovative Technologies in Social Science, 2023)
The following article aims to give brief information about the queer community and individuals in Baku city, Azerbaijan. The paper includes historical views and interviews with LGBTQI+ individuals in mentioned geography. The changes within years have analyzed briefly. The interviews with community individuals brought insights and reflections about the investigated topic. All in all, the paper represents a piece of brief but fruitful information to understand the queer life and societal mental values within the frames of the Azerbaijan Republic. The Caucasus region’s queer community is complex and most oppressed.